Analisis Rentabilitas Industri Pengolahan Kecap CV. Aneka Guna Di Kota Langsa - Widyawati Widyawati (Jurnal Agrisep, 2014)
Abstract. Soy industry as one of the downstream agribusiness industries can encourage the increasing of soybean production in Aceh. The existences of fairly large agroindustry perceive a role in economic development, especially the development of food crops in this area. This study aimed to determine the business feasibility through its profitability. Profitability of a soy industry shows the comparison between the net income and capital used in industry level. The research result showed that the ability of industry to gain net income is 23.97 persen, greater than the interest rate 18persen per year. Thus the soy processing industry CV. Aneka Guna is beneficial to be implemented. The amount of net benefit was IDR 108.59 million/year and the amount of capital needed was IDR 453 million /year. This industry provides favorable result in terms of profitability, where the percentage of net benefit gained by industry was 23.97persen per year from each of 100persen of capital employed.